Differences-in-Differences Analysis on the Impact of Direct Cash Transfer 2007-2008 for Fish Consumption Pattern - Paradizsa, Irlandi; Moeis, Jossy Prananta (Journal of Business and Economics Research (JBE), 2024)
Fisheries in Indonesia has a huge potential that if were to be developed adequately will help boost the economic growth. The potential is substantial, however the level of consumption still low compared to other country with lower fisheries potential. To find ways in developing the fisheries sector, this research would like to study the impact of shock of income—through the direct cash transfer—towards the fish consumption level. By understanding this, policymaker would be better equipped on finding the right program to increase its level of consumption in Indonesia. This research is using the quantitative method through the differences-in-differences analysis in finding the impact of income shock towards the fish consumption pattern by seeing the differences before and after the direct cash transfer program were carried out. The data used for this research came from the Indonesian Family Life Survey (IFLS) wave 3 to 5. In order to increase the validity of the result, this research used the Heckman Selection Model to reduce the potential bias. The result of this research finds that the impact of the direct cash transfer—as an income shock—actually lower the level of fish consumption amounting to Rp 326,25. There are several possibilities as to why this is happening, which are: (1) the elasticity of income for fisheries sector; (2) the status of fish as inferior goods for Indonesian; and (3) huge potential does not translate into a cheaper price for consumption.